Biomedical profile of gentamicin intoxication in goats - KUMAR, RAKESH; PANDEY, N N (The Indian Journal of Animal Sciences, 2013)
Subclinical toxicity was induced in 5 goats by i/m gentamicin@ 35 mg/kg b wt daily in 2 divided doses for 10 days. Serum analysis revealed marked elevation in uric acid concentration without any alteration in the levels of urea nitrogen (UN) and creatinine (CR). There were significant increases in serum alkaline phosphatase (ALP) activity and decrease in serum total protein, sodiUm and potussium levels. Serum calcium and inorganic phosphorus levels remained largely unaltered. Urinalysis revealed significant decrease in specific gravity, mild proteinuria (1+), few granular/ epithelial casts and markedly increased activity of ALP without any alteration in the concentration of UN, Cr and Pi. Most of the alterations in different parametres of serum and urine samples were recorded on day 10 followed by their gradual return to normal values suggesting recovery of Animuls from the toxic effect of gentamicin after its withdrawal. The detcrmination of urine ALP activity for diagnosis of renal insufficiency was found to be a dependable test even in cases of subclinical nephrotoxicity.